Enhancement of data retrieval performance for i-Learn Web Analytic System / Mohd Shahrizan Mohd Sa'at - Mohd Sa'at, Mohd Shahrizan (Faculty of Computer and Mathematical Sciences, 2007)
In the modem computing, database is one of the important aspects of it. Every system is using database whether it is small or complex. Database stores data and the system can modify it according to the needs such as insert, delete or update data. The volume of the data stored in a database is various between each database. It is ranging from several data and up to hundred thousands and even millions of data per database especially or the web based system. The web based system is usually used by anyone at everywhere in every time in the world. Web based system such as www.lelong.com.my for example record each day activities done by the user. This makes the database become very large as data was continuously inserted. So the performance of the database must be good enough to ensure the data processing doesn't take too much time. i-Leam system is a web based system developed for Mara University of Technology e-learning system. Each transaction made in this system is recorded and that's make its database's size increasing each time a single transaction is made. I-Leam system has a subsystem named i-Learn Web Analytic System that generate report of the activities made in the system by user for the administrator. As the database is very big with millions of data, the performance of the database must be good so that the report generating time can be reduced. This research will identify the available methods to enhance the database performance and implement it to the i-Leam Web Analytic System to enhance the performance of its database.